Prevention of Haemophilus influenzae type b (Hib) meningitis and emergence of serotype replacement with type a strains after introduction of Hib immunization in Brazil - Ribeiro, Guilherme S. (2003)
Surveillance for Haemophilus influenzae meningitis cases was performed in Salvador, Brazil, before and after introduction of H. influenzae type b (Hib) immunization. The incidence of Hib meningitis decreased 69% during the 1-year period after initiation of Hib immunization (from 2.62 to 0.81 cases/100,000 person-years; P<.001). In contrast, the incidence for H. influenzae type a meningitis increased 8-fold (from 0.02 to 0.16 cases/100,000 person-years; P=.008). Pulsed-field gel electrophoretic analysis demonstrated that H. influenzae type a isolates belonged to 2 clonally related groups, both of which were found before Hib immunization commenced. Therefore, Hib immunization contributed to an increased risk for H. influenzae type a meningitis through selection of circulating H. influenzae type a clones. The risk attributable to serotype replacement is small in comparison to the large reduction in Hib meningitis due to immunization. However, these findings highlight the need to maintain surveillance as the use of conjugate vaccines expands worldwide.